ANALYSIS OF RISK FACTORS POSTPARTUM HEMORRHAGE AMONG MOTHERS IN THE DELIVERY ROOM OF RSUD dr. ZAINOEL ABIDIN BANDA ACEH IN 2023 - Dewi Faridha; Miftahul Jannah; Nurnarita Laila; Maifrizal (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Globally, efforts to reduce the Maternal Mortality Rate (MMR) are a top health priority. It is estimated that around 70% of maternal deaths are due to bleeding. Hemorrhage happened in time postpartum. Obstetric complications in Aceh Province were 20.3% and 32 cases were due to bleeding. This study aims to analyze risk factors for incidents Postpartum Hemorrhage to the mother in the delivery room at RSUD dr. Zainoel Abidin (RSUDZA) Banda Aceh in 2023.Research design used correlational, using quantitative methods, with approach cross-sectional. Located in the Maternity Room at RSUD dr. Zainoel Abidin Banda Aceh in 2023. The population and sample in the study were all maternal data postpartum in January - June 2023 there will be 138 people in the maternity ward at RSUDZA Banda Aceh. Random sampling technique total population. Data collection tools use sheets checklist patient medical record data. Data analysis using logistic regression test to calculate the Odds Ratio with a 95% confidence level, using the STATA 13 program. The results showed that there was a significant relationship between: maternal age (p=0.000; OR=11.00), parity (p=0.000; OR=7.72), pregnancy interval (p=0.001; OR=3.2) , type of delivery (p=0.000; OR=42.6), birth canal injury (p=0.036; OR=2.2), birth weight (p=0.000; OR=23.51) with the incidence postpartum hemorrhage to mothers in the delivery room at RSUDZA Banda Aceh in 2023. This study identified a number of risk factors for postpartum hemorrhage. Optimizing activities screening These factors can reduce the incidence postpartum hemorrhage. To prevent this from happening postpartum hemorrhage It is hoped that health workers in the RSUDZA maternity room can improve the quality of health services and the community must be more cooperative in carrying out early detection of bleeding during pregnancy.